An Inclusive Workplace Approach to Disability through Assistive Technologies: A Systematic Review and Thematic Analysis of the Literature - Tiziana Marinaci; Claudio Russo; Giulia Savarese; Giovanna Stornaiuolo; Filomena Faiella; Luna Carpinelli; Marco Navarra; Giuseppina Marsico; Monica Mollo (Societies, 2023)
To explain the low employment rates of people with disabilities (PwDs), emerging debates have revealed an unexploited potential impact of assistive technology (AT) on human talent and the inclusion process. This article provides a systematic review to critically evaluate the current trends in the literature on AT. A systematic review was performed according to the inclusion criteria of the PRISMA-S guidelines, followed by a thematic analysis identifying the main themes by which the literature on the subject is organized. Finally, the Human Activity Assistive Technology (HAAT) model was used to deepen the contents taken into consideration in the scientific literature and to discuss the concept of workplace inclusion and its use. Forty-one studies fully met the eligibility criteria of the systematic review. The thematic analysis produced four clusters related to the impact and characteristics of AT in the workplace. Overall, the use of the HAAT model highlighted a lack of studies on the affective and socio-cultural dimensions that characterize the use of AT in the workplace. It is concluded that the deployment of AT can and should work on multiple levels to shape the workplace experiences of PwDs.